EFFECTIVENESS OF TICAGRELOR COMPARED TO CLOPIDOGREL IN REDUCING THE RISK OF MAJOR ADVERSE CARDIOVASCULAR EVENTS IN PATIENTS WITH CORONARY HEART DISEASE AFTER PERCUTANEOUS CORONARY INTERVENTION - NUR’AMIN, Hendra Wana; Dwiprahasto, Iwan; Kristin, Erna (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Antiplatelet therapy is recommended in patients with coronary heart disease (CHD) who had the percutaneous coronary intervention (PCI) procedure to reduce major adverse cardiovascular events (MACE). There has been a lack of population-based studies that showed the superior effectiveness of ticagrelor over clopidogrel and similar studies have not been conducted in Indonesia yet. The aim of the study was to investigate the effectiveness of ticagrelor compared to clopidogrel in reducing the risk of MACE in patients with CHD after PCI. Methods: A retrospective cohort study with 1-year follow-up was conducted. 361 patients consisted of 111 patients with ticagrelor exposure and 250 patients with clopidogrel exposure. The primary outcome was MACE, defined as a composite of repeat revascularization, myocardial infarction, or all-cause death. The association between antiplatelet exposure and the MACE was analyzed with Cox proportional hazard regression, adjusted for sex, age, comorbid, PCI procedures and concomitant therapy. Results: MACE occurred in 22.7% of the subjects. Clopidogrel had a significantly higher risk of MACE compared with ticagrelor (28.8%, vs 9.0%, hazard ratio (HR): 1.96 (95% CI 1.01 to 3.81, p=0.047). There were no significant differences in risk of repeat revascularization (20.40% vs 5.40%, HR: 2.32, 95% CI 0.99 to 5.42, p = 0.05), myocardial infarction (11.60% vs 3.60%, HR: 2.08, 95% CI, 0.73 to 5.93, p = 0.17), and death (1.60% vs 1.80%, HR: 0.77, 95% CI, 0.14 to 4.25, p = 0.77). Conclusion: Clopidogrel had a higher risk of MACE compared to clopidogrel in patients with CHD after PCI, but there were no significant differences in the risk of repeat revascularization, myocardial infarction, and all-cause death.Â 